PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI ISLAM SINKRONISASI DENGAN KEBIJAKAN KERANGKA KUALIFIKASI NASIONAL INDONESIA (KKNI) - Khotibul Umam (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This article discusses the development of the Islamic Higher Education curriculum (PTKI), in particular, becomes a necessity while still paying attention to the specific aspects of PTKI with the synchronization of the Indonesian National Qualifications Framework Policy (KKNI). That way, PTKI graduates are expected to be able to meet the demands of the job market and the needs of other stakeholders and can take part in social life and international relations by showing character as Muslim professionals. The description of the discussion in this article consists of the notion of curriculum and its development, the essence of curriculum development, models and principles of curriculum development, national policies on higher education curriculum goals and steps for curriculum development and approaches in developing Islamic education curriculum. Curriculum development policy towards Indonesia's national qualification framework in the field of higher education is a qualification leveling framework that can juxtapose, equalize and integrate learning outcomes in formal education, informal education and or work experience into types and levels of higher education. The Indonesian National Qualifications Framework (KKNI) serves as a reference in compiling the learning outcomes of graduates from every level of education nationally. Conceptually, each qualification level in the IQF is composed of four main parameters, namely (a) work skills, (b) scope of knowledge/knowledge, (c) methods and level of ability in applying the knowledge/knowledge and (d) managerial abilities.